Tornado alley - Kennedy, Marlane; Madrid, Erwin (New York, NY : Scholastic Inc., 2014)
Although Wyatt is not happy that he has to entertain his visiting cousin, he soon has much bigger problems to worry about when two tornadoes strike the area.
Keywords: Tornadoes -- Fiction; Cousins -- Fiction; Ranch life -- Fiction; Survival -- Fiction; Tornadoes -- Juvenile fiction; Cousins -- Juvenile fiction; Ranch life -- Juvenile fiction; Survival -- Juvenile fiction; Cousins; Ranch life; Survival; Tornadoes; Oklahoma -- Fiction; Oklahoma -- Juvenile fiction; Oklahoma; Fiction; Juvenile works